2021
DOI: 10.1038/s41598-021-81976-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of laser actions by bird’s feathers with photonic crystals

Abstract: Random lasers had been made by some biomaterials as light scattering materials, but natural photonic crystals have been rarely reported as scattering materials. Here we demonstrate the ability of natural photonic crystals to drive laser actions by sandwiched the feathers of the Turquoise-Fronted Amazon parrot and dye between two plastic films. Parrot feathers comprise abundant photonic crystals, and different color feathers compose of different ratios of the photonic crystal, which directly affect the feather … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, the RLs demonstrated a low loss, which was attributed to the weak absorption of the skeleton. Recently, Chen et al reported random lasing from the photonic crystal of butterfly wings [16] and parrot feathers [17] embedded with pyrromethene (PM597) dye. It was also shown that the quasi-periodic arrangement of textures on the butterfly wings and parrot feathers could effectively scatter light for random emission.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the RLs demonstrated a low loss, which was attributed to the weak absorption of the skeleton. Recently, Chen et al reported random lasing from the photonic crystal of butterfly wings [16] and parrot feathers [17] embedded with pyrromethene (PM597) dye. It was also shown that the quasi-periodic arrangement of textures on the butterfly wings and parrot feathers could effectively scatter light for random emission.…”
Section: Introductionmentioning
confidence: 99%
“…This can be useful in a variety of applications, such as noise reduction in buildings, acoustic isolation in machinery, or soundproofing in vehicles. This effect is similar to the photonic bandgap in optics, 13,40 which refers to a range of frequencies in which electromagnetic waves are strongly absorbed or reflected by a material or structure.…”
Section: Resultsmentioning
confidence: 82%
“…This can be useful in a variety of applications, such as noise reduction in buildings, acoustic isolation in machinery, or soundproofing in vehicles. This effect is similar to the photonic bandgap in optics, 13,40 which refers to a range of frequencies in which electromagnetic waves are strongly absorbed or reflected by a material or structure. We can find that except for a single bandgap of the primitive-based lattice, other TPMS-based structures show multiple acoustic bandgaps in the sub-2000 Hz frequency range.…”
Section: Resultsmentioning
confidence: 88%
“…4, the barbules of the green feathers were dark grey and, most likely, the melanin stored in the barbules absorbed the laser radiation causing thermal damage and discoloration. Note that red and yellow feathers also contain some melanin granules but these are embedded deeply within the barbules [51] (when viewed with the microscope, the barbules of red and yellow feathers were red and yellow respectively, not grey). The green colour of feathers is the result of the presence of biopigments, but also structural effects.…”
Section: Determining the Feathers' Damage Threshold Fluence For The N...mentioning
confidence: 99%